ANALISIS FAKTOR INTERNAL PERUSAHAAN TERHADAP NILAI PERUSAHAAN DI SEKTOR ENERGI - Nurhidayati Dwiningsih; Dea Adinda Syahwa Avrilla (Universitas Trilogi, 2026)
A phenomenon in 2022 in the energy sector indicated that company value, as measured by Price Book Value (PBV), decreased while stock prices experienced significant increases. This study aims to determine the effect of Corporate Social Responsibility (CSR), Return on Equity (ROE), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on Price Book Value (PBV) in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2024 period. The sample was selected based on the criteria that the companies were listed on the IDX during the study period and reported financial statements and published sustainability reports. The t-test results indicate that DER partially has a positive and significant effect on PBV, while the other three variables (CSR, ROE, and TATO) have no partial effect on PBV. Investors are advised to pay attention to the capital structure of listed companies, specifically DER, which indicates proportional and effectively managed debt usage, which can increase market confidence in the company's performance.Keywords: Corporate Social Responsibility (CSR), Debt to Equity Ratio (DER), Price Book Value (PBV), Return on Equity (ROE), Total Asset Turnover (TATO).